Economical Factors and their Impact on Marketing Activities in the Age of a Digital - Behavioral Economics Perspective - Kozielski , Robert (Studia Oeconomica Posnaniensia, 2018)
The achievements of behavioral economics have questioned the rationality of customers' behavior in the contemporary business environment and undermined the legitimacy of some economic laws. However, modern companies that operate and which are based on the model of internet platforms prove that the traditional approach to running a market game does not deliver expected results. The aim of the paper is to identify to what extent traditional economic theories are used in contemporary marketing, particularly in the area of customer behavior. The analysis of the data confirmed the declining role of classical economic laws and their impact on consumer choices, and has pointed to the need and importance of further research.